Human rights education and the post secular turn - Bowie, Bob (Journal of beliefs and values, 2012)
This article questions whether human rights education (HRE) scholarship is responding adequately to the post secular turn in thinking about the place and nature of religion in society. Here the post secular turn is used to describe the discrediting of secularisation theory, the recognition of religion as an enduring and pervasive global cultural force, and the resulting emergence of a discourse that concedes different secularities and multiple modernities. This article identifies the turn, notes the emerging discourse and identifies the lack of an adequate response in UK HRE scholarship which seems wedded to an increasingly outdated theory of secularisation. It concludes by considering alternative possible resources for a more adequate response.